An evaluation of thermoplastic composite fillers derived from construction and demolition waste based on their economic and environmental characteristics. (20th January 2021) - Sormunen, Petri; Deviatkin, Ivan; Horttanainen, Mika; Kärki, Timo
Abstract: The use of waste is often justified by the economic and environmental benefits of their use. This study compares the use of waste materials derived from construction and demolition waste—namely wood waste, mineral wool waste, gypsum board waste, and stone cutting dust—as alternative fillers in the production of thermoplastic composites using recycled high-density polyethylene as a matrix material. In total, nine alternative composites were studied in terms of their production costs, as well as their climate change impacts in three distinct product applications. Compared with the plastic matrix, the wood fiber achieved a cheaper price of €0.8–1.2/kg and the best properties in relation to weight. The price of mineral-based fillers varied between €0.5–1.1/kg, but the effect of the higher density on the weight increased the total price of the products. The unfilled recycled plastic was the cheapest solution in the application where the covered volume was important. The impact of using recycled high-density polyethylene in composites production totals at −1.24 kg CO2-eq./kg, out of where 1.75 kg CO2-eq. is the avoided impact from avoided waste disposal and 0.51 kg CO2-eq. is induced impact from producing the composites. When also accounting for the avoided impact from the substitution of virgin high-density polyethylene with the recycled high-density polyethylene composites, the avoided impact further increases to −3.17 kg CO2-eq./kg. The mineral fillers with were preferable in the application where mass was important, however, had lower avoided impacts than unfilled polyethylene ranging between −2.06 kg CO2-eq. and −2.47 kg CO2-eq. Wood fiber filler was the preferred filler option in the application where the material properties were taken into account in the amount of required material, but resulted in the lowest cumulative avoided impacts ranging between −1.79 and −2.25 kg CO2-eq., with most of the avoided impact originating from the replacement of virgin high-density polyethylene. Highlights: Production on 1 kg of wood plastic composite from waste has a global warming potential of 0.44–0.51 kg CO2 -eq. Global warming potential is −1.8 to −3.2 kg CO2 -eq along with the impact from avoided disposal and substitution. Construction and demolition wood was the best filler considering weight, cost and global warming potential of composite.